Atmospheric deposition fluxes of aluminium, iron and trace metals in a coastal station on the NW-Alboran Sea, (W-Mediterranean) - Liger-Pérez, Esperanza; Cañada, Pedro; Dueñas-Buey, Mª Concepción; Fernández, Mª Carmen; Cañete-Hidalgo, Sergio Andrés; Gordo Puertas, Elisa; Pérez-Martínez, Manuel (My University, 2014)
The atmospheric deposition over the whole Mediterranean is poorly constrained and hinders a clear assessment of the extent to which atmospheric elements of various anthropogenic and natural origins affect its biogeochemistry. Available data show poor spatial representation, as most of the deposition data refer to the northwestern zone. The Alboran Sea, in particular, is a very interesting case study as regards the atmospheric input because the atmospheric chemistry is dominated by antagonistic influences of natural (mainly from the Sahara) and human activity due to the relative proximity of land-based sources and densely populated shores. The biogeochemical impact of desert dust also remains a matter of discussion regarding its contribution for different major and minor elements to terrestrial and marine systems and especially its potential fertilizing role by supplying micronutrients as iron. Atmospheric fluxes of various trace metals were measured in order to evaluate the presence of these elements in their differently bio-available forms, contents in the soluble and non-soluble fractions were determined. Sampling presented for this study was performed in Malaga (southeast of Spain, 36° 43′ 40″ N; 4° 28′ 8″ W) in an open bulk deposition collector placed 10 m above the ground. The Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model was used to calculate the backward trajectories of air masses reaching the study region.
El estudio se ha realizado en el marco del Proyecto del Plan Nacional con ref. CTM12-37598-C02
Keywords: Deposición atmosférica; Atmospheric deposition; Trace metals; NW- Alboran Sea